United Kingdom Infrastructure Investment and Finance from a European and Global Perspective - INDERST, Georg (Journal of Advanced Studies in Finance; Vol 8 No 1 (2017): JASF Volume VIII Issue 1(15) Summer 2017, 2017)
This study provides an overview of UK infrastructure investment and finance in a longer-term, international perspective, yielding interesting facts and insights for both investors and policy makers worldwide. The UK is one of the leading countries in terms of private sector involvement in infrastructure, with several decades’ experience in regulating privatized utilities and in developing public-private partnerships (PPP). It has attracted substantial European and global capital, and London is a major market place for the infrastructure and green business. However, the UK has also seen decades of weak spending by the state (and taxpayers) on infrastructure. The country needs more investment when public budgets are already stretched. The question is whether private capital will be so easily available in future, especially from institutional and foreign investors.